Long-term prognosis of lupus nephritis: comparison between pediatric, adult, and advanced age onset - Calatroni, Marta; Andrulli, Simeone; Doti, Federico; Bello, Federica; De Vivo, Giovanni; Mastrangelo, Antonio; Del Papa, Nicoletta; Schioppo, Tommaso; Locatelli, Laura; Reggiani, Francesco; Moroni, Gabriella (Frontiers in Immunology, 2025)
Background and hypothesisLupus nephritis (LN) presents with varied outcomes depending on the age at diagnosis. We aimed to evaluate long-term kidney survival across three age groups.MethodsPatients were categorized based on their age at lupus nephritis diagnosis: ≤18 years (childhood), >18 to <45 (adulthood), and ≥45 years (elderly). The three groups’ CKD (eGFR <60 ml/min/1.73 m2 for at least 3 months) or death-free survival was estimated using Kaplan–Meier curves and compared with the log-rank test. To evaluate the independent prognostic role of age, adjusted for other predictors of chronic kidney disease (CKD) or death, we used multivariate Cox regression analysis.ResultsThis retrospective cohort study analyzed 260 patients followed for a median of 14.8 years. Of them, 46 (17.7%) were <18, 173 (66.5%) >18 and <45, and 41 (15.8%) ≥45 years old. 46% of elderly vs. 32.6% of children and 24.3% of adults had acute kidney disease (AKD) at diagnosis (P=0.02). Children had more active SLE, whereas the elderly had more chronic damage and hypertension. At 5, 10, and 20 years, CKD or death-free survival rates were 95.3%, 92.5%, and 88.4% in children; 98.2%, 90.1%, and 82.6% in adults; and 87.5%, 67.8%, and 53.5% in the elderly, respectively. Survival in elderly patients was significantly worse compared with children and adults (P= 0.001), whereas survival rates between children and adults were comparable (P = NS). At multivariate analysis, when the chronicity index was excluded from the model, older age emerged as an independent predictor of CKD or death (relative risk, RR: 3.278; CI: 1.402–7.662; P=0.006), with AKD (RR: 2.930; CI: 1.674–5.130; P<0.001), arterial hypertension (RR: 3.692; CI: 1.844–7.389; P<0.001), SLICC >0 (RR: 1.824; CI: 1.155–2.881; P=0.01), and failure to achieve complete remission at 1 year (RR: 4.784; CI: 2.355-9.716; P<0.001).ConclusionWhile children and adults demonstrate comparable long-term kidney survival, elderly patients face significantly worse outcomes due to advanced chronicity and systemic damage. These findings highlight the need for tailored interventions in late-onset LN. Older-onset LN, in fact, was an independent predictor of CKD or death together with AKD, arterial hypertension, SLICC >0, and no remission at 1 year.